2023
DOI: 10.3390/en16031466
|View full text |Cite
|
Sign up to set email alerts
|

Reinforcement Learning-Based Pricing and Incentive Strategy for Demand Response in Smart Grids

Abstract: International agreements support the modernization of electricity networks and renewable energy resources (RES). However, these RES affect market prices due to resource variability (e.g., solar). Among the alternatives, Demand Response (DR) is presented as a tool to improve the balance between electricity supply and demand by adapting consumption to available production. In this sense, this work focuses on developing a DR model that combines price and incentive-based demand response models (P-B and I-B) to eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 68 publications
0
5
0
Order By: Relevance
“…Typically, elasticity is negative, indicating an inverse relationship between electricity demand and electricity prices [39]. Several studies have investigated the price elasticity of demand for ADS [40][41][42]. In [43], the authors determined that price elasticities of demand can vary between −0.2 and −0.8, based on data and surveys conducted in the U.S.…”
Section: Demand Response Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…Typically, elasticity is negative, indicating an inverse relationship between electricity demand and electricity prices [39]. Several studies have investigated the price elasticity of demand for ADS [40][41][42]. In [43], the authors determined that price elasticities of demand can vary between −0.2 and −0.8, based on data and surveys conducted in the U.S.…”
Section: Demand Response Managementmentioning
confidence: 99%
“…In [43], the authors determined that price elasticities of demand can vary between −0.2 and −0.8, based on data and surveys conducted in the U.S. Furthermore, in [40,42], it was concluded that electricity demand is more elastic during peak hours compared to off-peak hours, making DR an efficient resource for enhancing system safety and quality during times of high stress.…”
Section: Demand Response Managementmentioning
confidence: 99%
“…RL's application in smart grids has been growing steadily. Researchers [1][2][3][4][5] have used RL to improve various aspects of smart grid management, including demand response, load balancing, and energy storage. Despite these advancements, there are still limitations in current approaches that hinder optimal energy efficiency: ➢ Limited Flexibility: Traditional smart grid control systems often use static rules or models, which are not easily adaptable to changing grid conditions.…”
Section: Introductionmentioning
confidence: 99%
“…The architectural flexibility of SPP allows for the development of financial incentives tailored to unique contexts, maximizing profit margins for both MNOs, the one that signed a contract with the end user and the one that will act as a temporary provider. The SPP module utilizes the reverse auction theory from the game theory family implemented with reinforcement learning [4], in order to return the maximum incentive profit for both the original and the new alternative provider. The choice of deep reinforcement learning [5] to implement the reverse auction theory boosts the scalability and reliability of the system and make it as fair as it can be for all the participants.…”
mentioning
confidence: 99%